The Influence of Tax Amnesty Program, Mobile Samsat Services and E-Samsat Program with Tax Socialization as Moderating Variable on Makassar City Samsat Revenue - Alfiah Nurhijrawati; Syamsuri Rahim; Junaiddin Zakaria (Universitas Muhammadiyah Makassar, 2024)
This study aims to examine. The effect of the Tax Bleaching Program, Mobile Samsat Services and the E-Samsat Program with Taxation Socialization as a Moderating Variable on Makassar City SAMSAT Revenue. The data in this study were obtained from taxpayers registered at SAMSAT Makassar City in 2022, namely motor vehicle taxpayers who were willing to become respondents. This study uses primary data by conducting direct research in the field by giving a questionnaire / statement sheet to respondents and drawing samples using the sIovin formula with a total of 100 taxpayer respondents. The data analysis technique was carried out by descriptive statistical analysis and PLS (Partial Least Square). The results showed that the Tax Bleaching Program had a positive and significant effect on Makassar City SAMSAT Revenue, Mobile Samsat Service had a positive and significant effect on Makassar City SAMSAT Revenue, E-Samsat Program had a positive and significant effect on Makassar City SAMSAT Revenue, Tax bleaching program with moderated by taxation socialization had a positive and significant effect, Mobile Samsat service with moderated by taxation socialization had a positive and significant effect and E-Samsat Program with moderated by taxation socialization had a positive and significant effect.